Three-dimensional printing of shape memory hydrogels with internal structure for drug delivery - Wang, Y.; Miao, Y.; Zhang, J.; Wu, J.; Kirk, Brett; Xu, J.; Ma, D.; Xue, W. (Elsevier, 2017)
© 2017 Elsevier B.V. Hydrogels with shape memory behavior and internal structure have wide applications in fields ranging from tissue engineering and medical instruments to drug delivery; however, creating the hydrogels has proven to be extremely challenging. This study presents a three-dimensional (3D) printing technology to fabricate the shape memory hydrogels with internal structure (SMHs) by combining sodium alginate (alginate) and pluronic F127 diacrylate macromer (F127DA). SMHs were constituted by a dual network structure. One is a stable network which is formed by F127DA photo-crosslinking; the other one is a reversible network which is formed by Ca 2 + cross-linked alginate. SMHs recovery ratio was 98.15% in 10 min after Ca 2 + was removed in the Na 2 CO 3 solution, and the elastic modulus remains essentially stable after the shape memory cycle. It showed that the drug releasing rate is more rapid compared with traditional drug-loaded hydrogels in in vitro experiments. The viability of 3T3 fibroblasts remained intact which revealed its excellent biocompatibility. Therefore, SMHs have a huge prospect for application in drug carriers and tissue engineering scaffold.